2011
DOI: 10.3390/ijms12074735
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Activity of Denture Soft Lining Material Modified by Silver Nanoparticles—A Pilot Study

Abstract: Soft liner materials in oral cavity environments are easily colonized both by fungi and dental plaque. These factors are the cause of mucosal infections. The microorganism that most frequently colonizes soft liner materials is Candida albicans. Colonization occurs on the surface of materials and within materials. A solution to this problem might involve modification of soft liner materials with silver nanoparticles (AgNPs). In this article, we present results showing the antifungal efficacy of silicone soft li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
106
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(110 citation statements)
references
References 35 publications
2
106
0
2
Order By: Relevance
“…31,32 The efficacy of silver nanoparticles against C. albicans has been confirmed in some commercial dental materials. 33 Nevertheless, to the authors' knowledge, no study to date has attempted to modify synthesized acrylic resins containing silver nanoparticles for dentures, or confirm an antifungal effect against C. albicans and cytocompatibility.…”
Section: Resultsmentioning
confidence: 99%
“…31,32 The efficacy of silver nanoparticles against C. albicans has been confirmed in some commercial dental materials. 33 Nevertheless, to the authors' knowledge, no study to date has attempted to modify synthesized acrylic resins containing silver nanoparticles for dentures, or confirm an antifungal effect against C. albicans and cytocompatibility.…”
Section: Resultsmentioning
confidence: 99%
“…4 The nanoparticles showed potent antibacterial activity and a significantly higher synergistic effect with erythromycin, methicillin, and ciprofloxacin. 5 Silver nanoparticles are also reported to possess antifungal, 6 anti-inflammatory, 7 antiviral, 8 anti-angiogenesis, 9 and antiplatelet 10 activities. They all confer to them a major advantage for the development of alternative products against, for example, multidrug-resistant microorganisms.…”
Section: Introductionmentioning
confidence: 99%
“…The results of this study found that PMMA-AgNPs significantly reduced the adherence of C. albicans, while flexural strength of PMMA was decreased (Acosta-Torres et al, 2012;Sodagar et al, 2012). The colonization of the soft lining of denture material by oral fungi could result in infections and stomatitis, and therefore AgNPs were incorporated into composites as antimicrobial agents in order to reduce the microbial colonization of lining materials (Grzegorz et al, 2011;Chladek et al, 2013). Bacterial adhesion to the surface of implants may result in peri-implant diseases and cannot always be avoided by sterilization before implantation.…”
Section: Discussionmentioning
confidence: 91%